Demographic Profile and Clinical Manifestations of Scabies Among Boarding School Students - Septiana Widyantari; Yuri Widia; Damayanti; Bagus Haryo Kusumaputra; Muhammad Yulianto Listiawan; Anang Endaryanto; Cita Rosita Sigit Prakoeswa (Faculty of Medicine, Universitas Airlangga, 2026)
Background: Scabies, a contagious skin disease, remains a global health problem to date. Based on the Global Burden of Diseases Study, Indonesia ranked 1st in 2015 and 3rd in 2021. This disease affects everyone regardless of age, sex, race, or socioeconomic status. Children and the elderly are the most vulnerable groups. Specific communities, such as dormitory residents, also have a higher risk of contracting scabies. The high prevalence of scabies among children in boarding schools deserves special attention. Purpose: To describe demographic characteristic and clinical manifestations of scabies among boarding school students. Methods: This observational cross-sectional study evaluated age, nutritional status (based on measurements of body weight, height, Body Mass Index (BMI), duration of stay in the boarding school, duration of illness, extent of affected body area, and variations in clinical symptoms. Result: A total of 41 male students with a mean age of 13.27 years were included in this study. Based on BMI-for-age-Z score (BAZ) assesment, majority (90.2%) had normal nutritional status. Regarding duration of illness, 25 individuals (61%) reported symptoms for ≤1 month, while 16 individuals (39%) experienced symptoms for > 1 month. Most participants (39 students ;95%) had stayed in the boarding school for > 3 months. In term of clinical manifestations, based on the extent of affected body areas, 22% of cases were classified as moderate, and 78% as severe. Conclusion: Fortyone individuals with a mean age of 13.27 years and good nutritional status exhibited clinical features categorized as moderate and severe.